Diversity and abundance of insect pest of low land rice field in Lamahi, Dang district of Nepal - Gyawali, Anjali; Regmi, Bandana; Pudasaini, Rameshwor; Acharya, Namuna (Journal of Agriculture and Natural Resources, 2019)
A study on diversity and abundance of insects in rice field was conducted at farmer field of Lamahi, Dang during July to October in 2019. Insects were collected using sweep net and light trap. Overall, 414 insect specimen representing 11 families and 8 orders were collected during the period. Grasshopper (23.98%) with including all species was the most abundance insect found in rice field as it followed by brown plant hopper (16.62%). Among the eight insect orders captured Orthoptera (29.16%) was the most abundance insect order followed by Homoptera (16.62%). As the diversity of insect pest in this area may responsible economic losses was found which will be useful to adapt appropriate management practices to keep them at normal area. The presence of natural enemies should conserve to enhance the natural biological control of insect pests.